2017
DOI: 10.1080/14658011.2017.1357868
|View full text |Cite
|
Sign up to set email alerts
|

The fracture toughness of natural fibre- and glass fibre-reinforced SMC

Abstract: The fracture toughness properties, in terms of stress intensity factor K Ic and strain energy release rate G Ic , of hemp fibre mat-reinforced sheet moulding compound (H-SMC) are measured using the compact tension (CT) method and compared with those of glass fibre-reinforced SMC (G-SMC). Three material parameters were considered for composite optimisation: fibre volume fraction, CaCO 3 filler content and hemp fibre surface treatments using either alkaline, silane or a combination of these two treatments. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…After trimming, the leaves were divided into strips along their length. Hand labor was used to extract the fibers (Figure 2), which were subsequently dried in the sun after being cleaned of dust with pure water [9,10].…”
Section: Sisal and Extraction Process Of Sisal Fibersmentioning
confidence: 99%
“…After trimming, the leaves were divided into strips along their length. Hand labor was used to extract the fibers (Figure 2), which were subsequently dried in the sun after being cleaned of dust with pure water [9,10].…”
Section: Sisal and Extraction Process Of Sisal Fibersmentioning
confidence: 99%
“…Surface treatment conditions followed previous work. [28][29][30] Alkaline treatment. Pre-dried hemp fibre mats were immersed in a 2 wt% NaOH solution for 1 h and subsequently rinsed in distilled water several times.…”
Section: Fibre Surface Treatmentsmentioning
confidence: 99%
“…Previous studies already showed that particularly a combined alkaline-silane treatment resulted in a significant increase in work of fracture, tensile and impact strength of H-SMC. [28][29][30] Treatment of hemp fibres with alkaline removed impurities from the waxy fibre surface, resulting in more sites for subsequent silane molecules to form bonds with the ligno-cellulose fibre surface, which in turn lead to a considerable increase in tensile strength 28 and work of fracture. 30 It should be noted that although composite strength typically requires a strong fibre-matrix interface, composite toughness usually requires an optimized rather than maximized interface.…”
Section: Influence Of Hemp Fibre Surface Treatmentmentioning
confidence: 99%
See 2 more Smart Citations